If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + 9) + 5 = -58 Reorder the terms: -7(9 + x) + 5 = -58 (9 * -7 + x * -7) + 5 = -58 (-63 + -7x) + 5 = -58 Reorder the terms: -63 + 5 + -7x = -58 Combine like terms: -63 + 5 = -58 -58 + -7x = -58 Add '58' to each side of the equation. -58 + 58 + -7x = -58 + 58 Combine like terms: -58 + 58 = 0 0 + -7x = -58 + 58 -7x = -58 + 58 Combine like terms: -58 + 58 = 0 -7x = 0 Solving -7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-7'. x = 0 Simplifying x = 0
| 19c+3d-6c+8d= | | 3(x+3)=6-14(x+5) | | 5y+y=5y+7 | | -a+5a=-53 | | 19x-6x=26 | | 9(x-3)+9=9x-17 | | 8x-1+5x+90=180 | | 25x^8/5x= | | 9=-3/8y | | 4/5w=-24 | | 42=-7/3y | | 0.14x+0.07(6000-x)=518 | | 53x-17-9x=18+44x-35 | | 53x-179x=18+44x-35 | | y=3x^2-15x-12 | | -5=x^2+4x | | 6x^6+6x-24= | | 2-4[4-(2y-5)]= | | 5000=(x+50)x | | 6x-3=(-4x+3) | | xb-6=cx+4 | | K/3-18=-26 | | 5*-5*25-5= | | 15x-10=6x-(x+2)+(3-x) | | -16x^2+78x+6=0 | | bx-6=cx+4 | | -8=3/7x | | h+2(h-6)=18 | | 10x+4y+5z=170 | | 4(x+3)=6(2x-5) | | -7/4c=-7 | | F(7)-f(4)/7-4 |